Peroxisome Proliferator-Activator Receptor γ: A Link between Macrophage CD36 and Inflammation in Malaria Infection - Yi Ren (PPAR Research)
Severe malaria infection caused by Plasmodium falciparum is a global life-threatening disease and a leading cause of death worldwide. Intensive investigations have demonstrated that macrophages play crucial roles in control of inflammatory and immune responses and clearance of Plasmodium-falciparum-parasitized erythrocytes (PE). This paper focuses on how macrophage CD36 recognizes and internalizes PE and participates the inflammatory signaling in response to Plasmodium falciparum. In addition, recent advances in our current understanding of the biological actions of PPARγ on CD36 and malaria clearance from the hosts are highlighted.